Actividades de enfermería para fomentar el autocuidado de los adultos mayores de la parroquia Tufiño basado en la Teoría de Dorothea Orem.” - Macias Cantos, Yiben Yiberly (2024)
Self-care allows accomplishing a better disposition and aptitude through the strengthening of the potential of autonomy to have an optimal aging process, for which the objective of this research is to develop nursing activities to promote self-care in elderly people in Tufiño parish, based on the theory of Dorothea Orem, using a methodology based on the quantitative approach, which was supported by descriptive research, bibliographic, action and field, in addition to using theoretical methods such as inductive-deductive, historical-logic, analytic synthetic and systemic approach. The instrument of the study was a questionnaire CYPAC AM, highlighting as main results significant problems regarding the selfcare of elderly people, given that 60% present inadequate self-care in physical activities, thus increasing the risk of loss of mobility, and 57% present insufficient nutrition. Additionally, in the category corresponding to sleep and rest the surveyed claimed to present alterations during their resting cycle, 60% have partially adequate or inadequate hygiene, for which it is possible to deduce that there exists inefficacy in the treatments of their pathologies; 41% evidenced deficiencies in the medical controls, limiting the early detection of diseases. In addictions and toxic habits, 57% were evidenced to be partially adequate or inadequate, affecting their general health condition. By using nursing activities, it was possible to promote self sufficiency in elderly people